Inoculation of growth-promoting bacteria in the lettuce crop - Ribeiro Machado, Fabiana; Ribeiro Machado, Fabio; Guimarães, Vandeir Francisco; de Moraes Echer, Márcia (Scientia Agraria Paranaensis, 2021)
Plant growth promoting bacteria (PGPB) are an alternative to increase the productivity of several crops, including lettuce. Several reports are found in the literature with the use of plant growth-promoting bacteria in lettuce cultivation, but most seek increments during the production of seedlings. Aiming to provide increments in the cultivation of lettuce in the field and to generate subsidies to technicians and producers, the present work aimed to study the influence of the application of commercial products based on Azospirillum brasilense, Bacillus subtilis + B. megaterium and Pseudomonas fluorescens, on agronomic characteristics and quality of crisp lettuce. The experiment was implemented in two locations, in a randomized block design, in a 4 x 3 factorial scheme, with four replications. The first factor refers to the application of different PGPB: control, without inoculation; inoculations with A. brasilense; B. subtilis + B. megaterium and P. fluorescens. The second factor was composed of three times of application of PGPB, the first being on the day of seedling transplantation (DAT), the second at 15 STR and the third on the day of seedling transplantation + 15 DAT. At 15 DAT, the relative chlorophyll content, plant height, head diameter, number of leaves per plant, leaf area, leaf dry mass, stem dry mass, root dry mass, total dry mass, root volume were evaluated. and root length. At harvest, the same variables analyzed at 15 DAT + leaf fresh mass, stem fresh mass, head fresh mass, root fresh mass, total fresh mass and leaf contents of nitrogen, phosphorus and potassium were analyzed. The inoculated plant growth-promoting bacteria did not promote a significant increase in the development of the lettuce cultivar Vera when compared to the control (without PGPB application).